Genomic alterations in the F8 gene correlating with severe hemophilia A in Egyptian patients. Issue 2 (20th December 2020) - Mosaad, Rehab M.; Amr, Khalda S.; Rabie, Eman A.; Mostafa, Naglaa O.; Habib, Sonia A.; El‐Kamah, Ghada Y.
Abstract: Background: Hemophilia A (HA) is an inherited X‐linked recessive coagulation disorder caused by factor VIII ( F8 ) deficiency. F8 rearrangements involving intron 22 (int22) and intron 1 (int1) account for almost half of severe HA phenotype also a hotspot exon 14 provides numerous mutational patterns. This study aims to identify F8 gene mutations among Egyptian HA patients. Methods: DNA samples from 60 HA patients were screened for int22 and int1 rearrangements using simplified inverse shifting PCR (IS‐PCR) followed by exon 14 sequencing. Also, four uncharacterized patients were studied by targeted exome sequencing. Results: In 33.3% of the studied patients, we identified three int22 rearrangements, three exon 14 mutations (two frameshift; one novel (NM_000132.3:c.2734_2735delAA, p.(N912Ffs*6)), a second reported mutation (NM_000132.3:c.3091_3094delAGAA, p.(K1031Lfs*9)), and one nonsense mutation (NM_000132.3:c.2440C>T, p.(R814*)). All identified mutations were detected in patients with severe HA phenotype. Targeted exome sequencing could not detect any known pathogenic variants. Conclusion: Intron 22 rearrangement and exon 14 mutations correlate with most severe hemophilia A Egyptian patients. Abstract : We identified three int22 rearrangements and three exon 14 mutations. Severe hemophilia A is associated with major disruptions of the F8 gene. Facing the high management cost, QoL, and limited resources in developing countries, the study is an important step to characterize the molecular pathology underlying hemophilia A.